Seven-month wintertime supplementation of 1200 IU vitamin D has no effect on hand grip strength in young, physically active males: A randomized, controlled study - Leho Rips; Alar Toom; Rein Kuik; Ahti Varblane; Hanno Mölder; Marika Tammaru; Mart Kull; Vahur Ööpik; Jüri-Toomas Kartus; Helena Gapeyeva; Madis Rahu (Taylor & Francis Group, 2022)
Background There has been a growing interest in the role of vitamin D for the well-being and physical performance of humans under heavy training such as conscripts in military service; however, there is a lack of long-term supplementation studies performed on members of this type of young, physically active, male population. The hypothesis of the study was that vitamin D supplementation during wintertime will decrease the prevalence of critically low vitamin D blood serum levels and increase hand grip strength during the winter season among young male conscripts. Study Design Longitudinal, triple-blinded, randomized, placebo-controlled trial. Methods Fifty-three male conscripts from the Estonian Army were randomized into two groups: 27 to an intervention group and 26 to a placebo group. The groups were comparable in terms of their demographics. The intervention group received 1200 IU (30 µg) capsules of vitamin D3, and the control group received placebo oil capsules once per day. The length of the follow-up was 7 months, from October 2016 until April 2017. Blood serum vitamin D (25(OH)D), parathyroid hormone (PTH), calcium (Ca), ionized calcium (Ca-i), testosterone and cortisol values, and hand grip strength were measured four times during the study period. Results The mean 25(OH)D level decreased significantly in the control group to a critically low level during the study, with the lowest mean value of 22 nmol/l found in March 2017. At that time point, 65% in the control group vs 15% in the intervention group had 25(OH)D values of less than 25 nmol/l (p < 0.001). In the intervention group, the levels of 25(OH)D did not change significantly during the study period. All other blood tests revealed no significant differences at any time point. The corresponding result was found for hand grip strength at all time points. Conclusion Long-term vitamin D supplementation during wintertime results in fewer conscripts in the Estonian Army with critically low serum vitamin D (25(OH)D) levels during the winter season. However, this did not influence their physical performance in the form of the hand grip strength test.